2005
DOI: 10.1097/01.don.0000140569.33867.bf
|View full text |Cite
|
Sign up to set email alerts
|

Periapical Inflammation after Coronal Microbial Inoculation of Dog Roots Filled with Gutta-Percha or Resilon

Abstract: A dog model was used to assess and compare in vivo the efficacy of gutta-percha and AH26 sealer versus Resilon with Epiphany primer and sealer [Resilon "Monoblock" System (RMS)] filled roots in preventing apical periodontitis subsequent to coronal inoculation with oral microorganisms. There were 56 vital roots in the premolars of seven adult beagle dogs aseptically instrumented, filled, and temporized. The roots were randomly divided into four experimental groups (Coronal Leakage Model) and one negative contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
0
27

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(194 citation statements)
references
References 16 publications
3
164
0
27
Order By: Relevance
“…26 The aim of this review was to analyse the literature assessing Resilon in order to investigate firstly whether it is a suitable root canal filling material and also whether it is an evidencebased alternative material to gutta-percha.…”
Section: N B R I E F General Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The aim of this review was to analyse the literature assessing Resilon in order to investigate firstly whether it is a suitable root canal filling material and also whether it is an evidencebased alternative material to gutta-percha.…”
Section: N B R I E F General Generalmentioning
confidence: 99%
“…26 The study was carried out over six months on seven Beagle dogs. It was concluded that there was a comparative reduction in apical periodontitis compared to gutta-percha; it must be stressed however that the authors had a financial interest in the Resilon system.…”
Section: Sealing Ability/leakagementioning
confidence: 99%
“…그 중에서 methylene blue를 이용한 색소침투법 은 다른 염색용액에 비해 분자량이 작아서 근관내로 더 쉽 게 침투된다고 알려져 있으며 36) butyric acid와 같은 세균 의 대사산물 크기와 유사하기 때문에 미세누출 실험에 가장 많이 사용된다 37) . Resilon을 이용한 근관충전의 밀폐효과에 대한 연구에서 Resilon이 gutta percha에 비해서 더 적은 미세누출을 나 타내고 12,38,39) , 치근단 밀폐능력을 더 향상시킬 수 있다고 하 였다 22,40) . 그러나 Resilon과 metacrylate based sealer를 이용한 근관충전은 gutta percha와 epoxy resin sealer를 이용한 근관충전 보다 더 낮은 치근단 밀폐능력을 보이고 41) , Resilon과 sealer 사이의 화학적 결합이 충분하지 않아서 낮은 전단결합강도를 나타내며 42) , 치근상아질과의 상호접착 강도도 떨어진다고 주장하는 연구자들도 있다 43) .…”
Section: ⅰ 서 론unclassified
“…2 Furthermore, the presence of moisture should not affect its sealing ability; it should be easy to use and should be radiopaque for visibility on radiographs. 3 Because existing root canal filling materials do not possess these ‘‘ideal’’ characteristics, Resilon was developed and recommended as a root canal filling material. Resilon has been recognized as a material that bonds to dentin when Epiphany sealer is used.…”
Section: Introductionmentioning
confidence: 99%